Wandlungen im Agrarlandschaftsbild Rheinhessens 1577-1950 - Ketzer, Günther (ERDKUNDE, 1954)
Using the oldest to the most recent maps indicating landuse the author sketches the history of the agricultural landscape of the town of Gau-Algesheim on the Rhine during the past four hundred years. The development of the land used for agriculture in this borough from medieval conditions to the present day, with problems of planning for the future use, is typical of the vine growing and market gardening districts of the Rhine.